PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP KETERAMPILAN MENULIS BERITA - Susanti, Edna; Ratna, Ellya; Zulfkarni, Zulfikarni (Universitas Negeri Padang, 2018)
The purpose of this study is to (1) desciribe the skill of writing the news berfore using cooperative learning model tipe think pair share, (2) desciribe the skill of writing the news after using cooperative learning model tipe think pair share, (3) describe effect between using of cooperative learning model type think pair share on the skill of writing to the news of class VIII SMP Pembangunan Laboratorium UNP. The result of this study is the influence of cooperative learning model type think pair share to news writing skill. Then, the model of cooperative learning type think pair share can be applied as an alternative in learning news writing skill.Â Kata kunci: pengaruh, model TPS, dan menulis berita